Architectural material and detail structure : Metal - Perez, Fernando (Mumbai Mehul book Sales, 2018)
The development of architectural materials has lasted for thousands of years. On one hand, we are always looking for materials and expressive techniques of historical and local background; on the other hand, we are constantly impressed by the state-of-the-art technology. Sheet metal is extensively used in architecture - like aluminium sheet, aluminium-plastic panel, color steel plate, copper plate, stainless steel plate, etc. - as there are multiple advantages: it is environment-friendly due to its high recovery percentage, its diversification in colors and forms enables various complex geometry patterns and textures, and how its weatherability and durability can adapt to most buildings' requirements. It is also capable of achieving different visual effects: smooth aluminium sheet and stainless steel plate reflect the beauty of modern technology, while copper plate realizes the integration of the present and the past. There are four chapters in this book: steel, aluminium, copper and zinc. Each chapter is further classified by the metal's specific forms. Through careful analysis, photos, detailed drawings, and informative text, it illustrates the characteristics of metal and its application in the detail structure. This book provides a practical reference for the application of metal in architectural design for architects and other readers alike.
Keywords: ARCHITECTURAL MATERIALS (AR-MAT)